Bis(tetrapropylammonium) di-μ(3)-iodido-di-μ(2)-iodido-diiodidodipyridinetetracopper(I) - Jalilian, Ehsan (International Union of Crystallography, 2010)
The title compound, (C(12)H(28)N)(2)[Cu(3.194)I(6)(C(5)H(5)N)(2)] was prepared from reaction of copper powder, copper(I) oxide, hydroiodic acid, tetrapropylammonium iodide and pyridine under hydrothermal conditions. In the centrosymmetric Cu(4)I(6) (2−) anion, one Cu site is in a trigonal-planar coordination while the second Cu site, which is only partially occupied [site occupancy of 0.5968 (16)], is surroundedby three iodine atoms and one pyridine molecule in a distorted tetrahedral coordination.